Review Manajemen Rantai Pasok Produk Pertanian Berkelanjutan: Konseptual, Isu Terkini, dan Penelitian Mendatang - Rachman Jaya; Yusriana Yusriana; Eka Fitria (Jurnal Ilmu Pertanian Indonesia, 2021)
Recently, the interest of academic and research institutions in sustainable agric-supply chain management (SASCM) has risen. This fact can be seen from the number of papers published as special issues. Agric-supply chain management is a substance deepening from conventional supply chain management which is discussing integration of economical, environmental, and social aspects to reach a goal of organization. The objective of this research was to describe the state of the art about this topic and future research issues. The number of papers analyzed were 111 articles published from 2003–2020. The articles were obtained from scientific provider such as Science direct, EBSCO, Cross-Reff, Researchgate, DOAJ, Academia.Edu, and Google Scholar. In this research, we cluster (SASCM) to several items such as supply chain management, sustainable supply chain management, and sustainable supply chain management for agricultural product. The content analysis was used to describe the state of the arts and novelty. The result of the study show that it is critical for the actors of agricultural business to apply sustainability concepts including economic, social, environmental, and institution on the systems of agricultural supply chain based on industry 4.0 approach to reach a sustainable business process. Synthesis and determination of main topics of research in the future is undertaken at the end. Keywords: agricultural product, management, sustainable supply chain